Twenty-one steps : guarding the Tomb of the Unknown Soldier - Gottesfeld, Jeff (Candlewick Press, 2021)
"With every step, the Tomb Guards pay homage to America's fallen. Discover their story, and that of the unknown soldiers they honor, through resonant words and illustrations. Keeping vigil at the Tomb of the Unknown Soldier, in Arlington National Cemetery, are the sentinel guards, whose every step, every turn, honors and remembers America's fallen. They protect fellow soldiers who have paid the ultimate sacrifice, making sure they are never alone. To stand there--with absolute precision, in every type of weather, at every moment of the day, one in a line uninterrupted since midnight July 2, 1937--is the ultimate privilege and the most difficult post to earn in the army. Everything these men and women do is in service to the Unknowns. Their standard is perfection. Exactly how the unnamed men came to be entombed at Arlington, and exactly how their fellow soldiers have come to keep vigil over them, is a sobering and powerful tale . . . that honors the soldiers who honor the fallen"--Provided by publisher.